ANALISIS MOTIVASI ORANG TUA PADA PENDIDIKAN ANAK DI DESA PAMPANG HARAPAN KABUPATEN KAYONG UTARA - Yani Yani; Aminuyati Aminuyati; Bambang Genjik Sumarton (Universitas Tanjungpura, 2019)
AbstractThe study aims to determine the Analysis of Parent’s Motivation in Children’s Education in Pampang Harapan Village, Sukadana District, North Kayong Regency. The method in this research was descriptive research study survey. The data source of this research was 8 parents who have children who are at school age, both elementary school, junior high school, senior high school, and college. The results of the research conducted show that, 1) The form of Parents' Attention to Children was measured by providing guidance categorized as very good (100%), whereas seen from giving rewards or prizes were categorized quite well (50%), 2) Providing Learning Facilities was categorized as good ( 75%), 3) Parental Supervision of Children in Supporting Children's Education, measured from monitoring children's academic development is categorized very well (87.5%), seen from supervising or accompanying children learning in the good enough category (62.5%) , whereas seen from the supervision of the association of children's activities can be categorized very well (87.5%). So, it can be concluded that Parents' Motivation in Children's Education in Pampang Harapan Village can be categorized as good (77.08%). Keywords: Children’s Educationn, Motivation, Parents